A Young Healthy Male with Spontaneous Subcutaneous Emphysema Occurring in Neck, Retropharyngeal and Mediastinal Spaces - Moayyad Malas; Nawaf Fatani; Zuhair Aljuhani (Case Reports in Otolaryngology)
We present a case of spontaneous cervical, retropharyngeal, and mediastinal emphysema occurring in a previously healthy young male, which is the first described case in Saudi Arabia. The patient was admitted to the ward for observation, monitoring of vital signs, analgesia, and prophylactic antibiotics. The patient was kept under observation for 8 days. During that time, neck pain improved gradually with no episodes of oxygen desaturation or vital sign deterioration. The patient was later discharged with very mild persistent pain. Two weeks after discharge, patient was seen in outpatient clinic and was free of symptoms. Spontaneous subcutaneous emphysema remains a rare presentation encountered in emergency department. The investigations and treatment required for such patients has no consensus between authors. Although most of the reported cases described an uncomplicated course, there is a need for clear guidelines on management protocol.